Local retinoic acid signaling directs emergence of the extraocular muscle functional unit - Comai, Glenda Evangelina; Tesařová, Markéta; Dupé, Valérie; Rhinn, Muriel; Vallecillo-García, Pedro; da Silva, Fabio; Feret, Betty; Exelby, Katherine; Dollé, Pascal; Carlsson, Leif; Pryce, Brian; Spitz, François; et al. (PLoS biology, 2020)
Coordinated development of muscles, tendons, and their attachment sites ensures emergence of functional musculoskeletal units that are adapted to diverse anatomical demands among different species. How these different tissues are patterned and functionally assembled during embryogenesis is poorly understood. Here, we investigated the morphogenesis of extraocular muscles (EOMs), an evolutionary conserved cranial muscle group that is crucial for the coordinated movement of the eyeballs and for visual acuity. By means of lineage analysis, we redefined the cellular origins of periocular connective tissues interacting with the EOMs, which do not arise exclusively from neural crest mesenchyme as previously thought. Using 3D imaging approaches, we established an integrative blueprint for the EOM functional unit. By doing so, we identified a developmental time window in which individual EOMs emerge from a unique muscle anlage and establish insertions in the sclera, which sets these muscles apart from classical muscle-to-bone type of insertions. Further, we demonstrate that the eyeballs are a source of diffusible all-trans retinoic acid (ATRA) that allow their targeting by the EOMs in a temporal and dose-dependent manner. Using genetically modified mice and inhibitor treatments, we find that endogenous local variations in the concentration of retinoids contribute to the establishment of tendon condensations and attachment sites that precede the initiation of muscle patterning. Collectively, our results highlight how global and site-specific programs are deployed for the assembly of muscle functional units with precise definition of muscle shapes and topographical wiring of their tendon attachments.
Keywords: Embryonic Development; signální transdukce; okulomotorické svaly; Tendons; Connective Tissue; myši inbrední C57BL; Mice, Inbred C57BL; Signal Transduction; šlachy; Mice; Morphogenesis; Tretinoin; zvířata; Oculomotor Muscles; zobrazování trojrozměrné; Mice, Inbred DBA; Eye; embryonální vývoj; myši; Imaging, Three-Dimensional; morfogeneze; oči; myši inbrední DBA; tretinoin; pojivová tkáň; Animals